2010
DOI: 10.1021/nl9037246
|View full text |Cite
|
Sign up to set email alerts
|

Drude Relaxation Rate in Grained Gold Nanoantennas

Abstract: The effect of grain boundaries on the electron relaxation rate is significant even for large area noble metal films and more so for plasmonic nanostructures. Optical spectroscopy and X-ray diffraction show a substantial improvement in plasmon resonance quality for square-particle nanoantennas after annealing due to an enlarged grain size from 22 to 40 nm and improved grain boundaries described by the electron reflection coefficient. The electron relaxation rate due to the grains is shown to decrease by a facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
185
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 183 publications
(193 citation statements)
references
References 24 publications
8
185
0
Order By: Relevance
“…In particular it has been shown that the plasmon linewidth of polycrystalline gold NPs is strongly affected by the grain size. 59 We conclude that the collection of polycrystalline NPs have intrinsic dephasing rates around 20% higher than singledomain NPs due to the electron scattering on their crystal defects. This result reveals the important and often neglected role of twins in determining the LSPR linewidth.…”
Section: Localized Surface Plasmon Resonancementioning
confidence: 79%
“…In particular it has been shown that the plasmon linewidth of polycrystalline gold NPs is strongly affected by the grain size. 59 We conclude that the collection of polycrystalline NPs have intrinsic dephasing rates around 20% higher than singledomain NPs due to the electron scattering on their crystal defects. This result reveals the important and often neglected role of twins in determining the LSPR linewidth.…”
Section: Localized Surface Plasmon Resonancementioning
confidence: 79%
“…The imaginary part of the dielectric function 2 ( Figure 1b,d,f) increases monotonically with increasing temperature for all heating cycles. However, for the first cycle the increase in 2 ( Figure 1b) is not uniform which is due to the annealing effects and grain movements that occur at high temperatures 27 . The increase in 2 is more uniform for the subsequent cycles (Figure 1d,f).…”
Section: Resultsmentioning
confidence: 96%
“…Thermal annealing [ 31 ] is utilized to improve the modulation depth of the Fano resonance or to turn off the coupling. In particular, we carry out time-dependent in-situ studies of the plasmonic spectra during heating.…”
Section: Doi: 101002/adma201202109mentioning
confidence: 99%